2010
DOI: 10.1371/journal.pone.0010186
|View full text |Cite
|
Sign up to set email alerts
|

Voreloxin Is an Anticancer Quinolone Derivative that Intercalates DNA and Poisons Topoisomerase II

Abstract: BackgroundTopoisomerase II is critical for DNA replication, transcription and chromosome segregation and is a well validated target of anti-neoplastic drugs including the anthracyclines and epipodophyllotoxins. However, these drugs are limited by common tumor resistance mechanisms and side-effect profiles. Novel topoisomerase II-targeting agents may benefit patients who prove resistant to currently available topoisomerase II-targeting drugs or encounter unacceptable toxicities. Voreloxin is an anticancer quino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 50 publications
(115 reference statements)
5
129
0
Order By: Relevance
“…Vosaroxin is a naphthyridine analog (Figure 1), structurally related to quinolone antibacterials, that exerts its anticancer activity exclusively by DNA intercalation and inhibition of topoisomerase II, leading to site-selective DNA double-strand breaks and apoptosis [26][27][28]. Vosaroxin is not a substrate for P-glycoprotein drug pumps, and can induce apoptosis independent of p53, thereby avoiding two common mechanisms of drug resistance [29].…”
Section: Research Papermentioning
confidence: 99%
“…Vosaroxin is a naphthyridine analog (Figure 1), structurally related to quinolone antibacterials, that exerts its anticancer activity exclusively by DNA intercalation and inhibition of topoisomerase II, leading to site-selective DNA double-strand breaks and apoptosis [26][27][28]. Vosaroxin is not a substrate for P-glycoprotein drug pumps, and can induce apoptosis independent of p53, thereby avoiding two common mechanisms of drug resistance [29].…”
Section: Research Papermentioning
confidence: 99%
“…Interest in the use of quinolone analogs as cytotoxics began after initial research showed that they have the potential to interact with mammalian topoisomerases [17][18][19][20]. Vosaroxin is a first-in-class cytotoxic quinolone derivative that intercalates in DNA and inhibits topoisomerase II (topo II) [21][22][23][24]. It has been shown to be a replication-dependent DNA damaging agent, causing irreversible G2 arrest and rapid apoptosis.…”
Section: Drug Evaluationmentioning
confidence: 99%
“…Vosaroxin has several advantages over these agents: more favorable pharmacologic properties, the potential to overcome resistance mechanisms and a stable quinolone core. Experimental data suggest that vosaroxin does not produce significant levels of reactive oxygen species (ROS) compared with doxorubicin [21], with extrapolated decreased risk of ROS-induced cardiotoxicity. These properties may hold the key to achieve meaningful outcomes when treating older patients and patients with relapsed and refractory chemo-resistant disease and will be reviewed in depth in this article.…”
Section: Drug Evaluationmentioning
confidence: 99%
See 2 more Smart Citations